Jeroboam's royal drama - Bodner, Keith (Biblical refigurations, 2012)
This text explores the characterization of Jeroboam in 1 Kings 11-14, tracing the rise and fall of this notorious figure. Close analysis of the Hebrew text reveals a literary achievement of great subtlety